Analysis of Baturagung Reservoir Leaking, Gedangrejo, Gunung Kidul Regency using Digital Outcrop Model Method - Farisan, Ardhan; Bahagiarti, Sari; Nurwantari, Nanda Ajeng; Setyaningrum, Tuti; Rahatmawati, Istiana; Zakaria, Muhammad Faizal; Probowati, Dyah (Badan Geologi, 2024)
Water, serving as a vital resource, finds applications in diverse sectors such as agriculture (irrigation), drinking watersupply, flood control, and hydroelectric power generation. On a smaller scale, the construction of